The role of nitric oxide in portal hypertension caused by extrahepatic portal vein obstruction - Goel P; Srivastava K; Das N; Bhatnagar V (Wolters Kluwer Medknow Publications, 2010)
Aims : Nitric oxide (NO) in peripheral venous blood has been shown to be elevated in experimental portal hypertension. This study aims to determine the serum NO levels in patients with extrahepatic portal venous hypertension (EHPVO) pre- and postoperatively and to analyze whether these can serve as a reliable and early indicator of shunt blockage or malfunction. Materials and Methods: During the period 2006-2010, 48 children with EHPVO were included in this prospective study; 40 underwent porto-systemic shunt and eight underwent splenectomy with devascularization. NO was evaluated preoperatively, 14 days after surgery, at 3 months and then 6 monthly thereafter. The median follow-up duration was 21 months. Shunt patency was confirmed with Doppler and computed tomography portography. Forty-eight age-matched children with hypospadias served as controls. Results : NO was higher in EHPVO patients as compared with controls (43.16 ± 16.27 vs. 5.76 ± 2.62 μmol/l) (P = 0.0001). There was a significant decline in the NO levels (4.64 ± 3.18 μmol/l) following shunt surgery (P = 0.0001), and it continued to remain low till the shunt was patent. A shunt block was indicated by rising NO levels in all five patients. The devascularization group also demonstrated a significant decline in the NO levels (27.06 ± 3.56 μmol/l) (P = 0.002), but it was less as compared with the shunted patients. The decline in the portal pressure after shunt surgery was found to correlate with the decline in the serum NO levels. Conclusions : The blood levels of NO can be used in the diagnosis of portal hypertension, and are useful for monitoring the patency of the shunt.